Improving English Speaking Competence Using Motivational Strategies - Dwi Lia Rakhmasari (UIN Raden Mas Said Surakarta, 2018)
In learning English, students need to have good attitudes toward the language. Teachers should make good atmosphere in the classroom so students become confident especially in speaking. Management students of STIE Putra Bangsa Kebumen are prepared to face ASEAN Economic Community (AEC). Unfortunately, they are lack of english speaking competence. This study proposes to solve that problem by applying Motivational Strategies. This research is a Classroom Action Research. The Researcher analyses in both qualitative and quantitative. In quantitative data, researcher compares the mean of pre-test and also post-test. In measuring students’ achievement, researcher uses the concept from Hudghes (2003). In qualitative data, the researcher does reduction, display and verification. The result of this research shows different number. The post-test mean increases from 60,72 to 79,68. This study will contribute as alternative strategies to improve the students’ English speaking capacity and possible to be applied by teachers from other subjects.